Plasmids coding for heat-labile enterotoxin production isolated from Escherichia coli O78: comparison of properties. - McConnell, M M (1980)
Nineteen enterotoxigenic Escherichia coli strains of serogroup O78, isolated in different geographical areas from humans with diarrheal diseases, were tested for their ability to transfer enterotoxin production. All of the strains originally produced heat-labile enterotoxin, and 16 also produced heat-stable enterotoxin and colonization factor antigen I. Plasmids coding for the production of heat-labile enterotoxin only were transferred from 13 strains. Some properties of these plasmids were compared. All were fi+, but they could be divided into three groups on the basis of their incompatibility reactions, ability to restrict E. coli K-12 phages, and size. The three heat-labile enterotoxin plasmids isolated from African strains all belonged to one enterotoxin plasmid group. The heat-labile enterotoxin plasmids from the Asian strains were divided into two groups, those from serotype O78.H11 differing from those from serotype O78.H12.